Generic and specific tourism resources in the countryside of Guelmim-Kingdom of Morocco - Dr. Malika AIT Nasser (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: Specific rural Guelmim province of Morrocco tourism attractions are highlighted here (south of Morocco). The study aims to defend this transition’s significance by focusing on the actor who can influence this key step in marketing a tourism resource. Methodology: The province of Guelmim in southern Morocco consists of 20 communes (18 rural and 2 urban) that serve as the basis for our study area’s geographical definition. To keep our research manageable, we focus on four rural communes: Assrir, Fask, Abaynou, and Amtedi. With all their peculiarities, the raw variety of resources can be traced through the qualitative analysis of comments from the surveyed literature. Institutional actors were consulted for this qualitative study, including tourism and culture delegates, municipal officials, the Regional Tourism Council, and tourism experts. Findings: From this vantage point, the operator’s role is seen as a prism through which the unique characteristics of the resource are conceptualized in its historical and cultural representatives, thereby highlighting the importance of the resource at the local territory. Implications/Novel Contribution: This article describes the unique rural tourism opportunities and its development to support economy. The study has widespread implications for tourism in several countries with similar geographical resources. .